2011
DOI: 10.5505/tjod.2011.14880
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Sleep Quality

Abstract: The data collected by face to face interview. "Patient Recognition Form" was used to collect information about individual socio-demographic characteristics and data about their pregnancy. Sleep quality was evaluated by using Pittsburgh Sleep Quality Index (PSQI), sleep apnea risk by Berlin Sleep Questionnaire and sleepiness by Epworth Sleepiness Scale. Observations: 86% of the pregnant women involved in our study were found to have bad sleep quality. It was determined that sleep quality in pregnant women is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
3
10
3
1
Order By: Relevance
“…In our study, younger mothers were more likely to have better quality of sleep (r s = −0.07). This trend was similar to a study conducted by Taskiran [9], showing that women aged between 29 and 45 year old had worse sleep quality than the age group between 17 and 28. However, as the sample size of our study was quite small, this difference might not reveal as significant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, younger mothers were more likely to have better quality of sleep (r s = −0.07). This trend was similar to a study conducted by Taskiran [9], showing that women aged between 29 and 45 year old had worse sleep quality than the age group between 17 and 28. However, as the sample size of our study was quite small, this difference might not reveal as significant.…”
Section: Discussionsupporting
confidence: 90%
“…It was suggested that several factors could influence sleep quality of maternal health. These were maternal age [9] [10], pre-pregnancy body mass index (BMI) [10] [11], gestational age [12] [13], gravida (the number of pregnancy) [14] and para (the number of pregnancy beyond 20 weeks of gestation) [15]. In particular, Sleep Hygiene Practices have linked good effects on sleep quality according to some research studies [16] [17] [18].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates for altered sleep quality during pregnancy range from 40% to 96%, depending on the population studied and the time of assessment being higher during the third trimester of pregnancy [ 8 – 12 ]. According to the result of different studies, increased age, advanced education, employment status, monthly income, gestational age, parity, alcohol consumption and smoking are found to be factors affecting the sleep quality of pregnant women [ 4 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic variables (such as maternal age, gestational age, gravida, parity, history of nausea vomiting, abortion history, education, employment and economic status) were reported to be associated with the incidence of nausea and vomiting in pregnant women (2,7,8) taken using a questionnaire filled out by the respondents themselves. While the variable severity of vomiting nausea was measured using Unique Quantification of Emesis and Nausea (PUQE) -24 scoring system developed by Ebrahimi, Maltepe, Bournissen, & Koren (9) and has been translated into Indonesian and used in previous research (10).…”
Section: Methodsmentioning
confidence: 99%